Investigation of the computerized tomography histogram analysis in distinction of distal ureteral stone and pelvic phlebolith - Tural, İbrahim Çağrı; Yurttutan, Nursel; Baykara, Murat; Kızıldağ, Betül (My University, 2021)
Aim: The aim of our study is to investigate the efficacy of the region of interest (ROI) and histogram analysis method in cases where distal ureteral stone and phlebolith distinction cannot be made in abdominal computed tomography (CT) with the stone protocol. Materials and Methods: A total of 100 adult patients (> 16 years old) with stones ?3 seen in the distal third of the ureter on their tomography and 100 adult patients with pelvic phleboliths ?3 were included in the study. For histogram analysis, the ROI measurement was conducted at the largest dimension with the most selectable edges using the hand-drawing tool. Results: A total of 100 adult patients (> 16 years old) with stones ?3 seen in the distal third of the ureter on their tomography and 100 adult patients with pelvic phleboliths ?3 were included in the study. For histogram analysis, the ROI measurement was conducted at the largest dimension with the most selectable edges using the hand-drawing tool. Conclusions: Histogram analysis can be used to differentiate between distal ureteral stone and pelvic phleboliths and may contribute to the diagnosis without additional examination. Keywords: Distal ureteral stone, phleboliths, computed tomography, histogram analysis.
Keywords: Genel ve Dahili Tıp; Patoloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme